In Search of Successful Inflation Targeting. - Miao, Yanliang (IMF Working Papers., 2009)
In a first attempt to treat inflation targeting (IT) as a continuous variable, we construct IT subindices for 21 full-fledged ITers on three dimensions: flexibility, transparency, and explicitness. Comparing flexibility and transparency we find that (1) the impact of flexibility on both the mean and variation of inflation is more quadratic than that of transparency; (2) after adding the transparency index, the impact of flexibility is no longer significant. The significant and negative association between transparency and the level and variation of inflation is confirmed when we check for robu.